Eculizumab refractory thrombotic thrombocytopenic purpura secondary to post-endoscopic retrograde cholangiopancreatography pancreatitis in a patient - Faizan Malik; Naveed Ali; Irfan Ahsan; Ali Raza Ghani; Christian Fidler (Greater Baltimore Medical Center, 2016)
Thrombotic thrombocytopenic purpura (TTP) is a rare multisystem microvascular disorder, which is characterized by pentad of thrombocytopenia, microangiopathic hemolytic anemia, and organ dysfunction due to occlusive thrombi. The proposed pathophysiology involves an imbalance between unusually large von Willebrand factor multimers and the cleaving protease ADAMTS13. Acute pancreatitis is a well-described consequence of TTP, but TTP secondary to acute pancreatitis is a rare phenomenon. We present a patient who developed TTP due to post-ERCP pancreatitis with hematologic, cardiovascular, pulmonary, and renal complications and is the first case of this kind. Despite early initiation of therapy, the patient did not recover making it among the 10% of cases of TTP that prove fatal despite appropriate therapy.